Evaluation of the utility of a rapid test for syphilis at a sexually transmitted disease clinic in Buenos Aires, Argentina - Gallo Vaulet, Maria Lucia (2018)
Even though syphilis can be easily diagnosed by simple and low-cost laboratory methods, it continues to be an important health problem. Rapid tests (RT) for the detection of treponemal antibodies can facilitate earlier diagnosis, access to treatment and linkage to care. The aim of this study was to analyse the usefulness of the incorporation of a RT in the detection of patients infected with T. pallidum in a sexually-transmitted disease (STD) clinic. Between March and December 2015, a syphilis RT was offered to patients who spontaneously attended the clinic. Conventional serology testing was additionally indicated to every participant. The RT for syphilis was offered to 1887 patients, of whom 31.1% agreed to get tested. VDRL test was performed in 84.0% of patients that were also tested with syphilis RT, with a significantly higher frequency observed among participants with reactive RT (94.3% vs. 79.8%, p < 0.001). These results showed that 33.7% of the participants were reactive for the RT and 27.0% were reactive for the VDRL test. Both tests were reactive in 24.9% and non-reactive in 64.3%. A high prevalence of active syphilis was detected in patients attending the clinic. The use of a syphilis RT had a positive impact, which in combination with the VDRL test increased the number of patients that were effectively diagnosed.